Revision of the squat lobsters of the genus Phylladiorhynchus Baba, 1969 (Crustacea, Decapoda, Galatheidae) with the description of 41 new species - Rodríguez-Flores, Paula C.; Macpherson, Enrique; Machordom, Annie (Zootaxa, 2021)
The genus Phylladiorhynchus Baba, 1969 currently contains 11 species, all occurring in the shallow waters and on the continental shelf of the Indian and Pacific oceans. Recent expeditions in these oceans have resulted in the collection of numerous new specimens in need of analysis. We have studied this material using an integrative approach analysing both morphological and molecular (COI and 16S) characters. We describe 41 new species and resurrect three old names: P. integrus (Benedict, 1902) and P. lenzi (Rathbun, 1907), previously synonymized with P. pusillus (Henderson, 1885), and P. serrirostris (Melin, 1939), previously synonymized with P. integrirostris (Dana, 1852). Most species of the genus are described and illustrated. Some species are barely discernible on the basis of morphological characters but are highly divergent genetically. Species of Phylladiorhynchus are mainly distinguishable by the number of epigastric spines and lateral spines of the carapace, the shape and the armature of the rostrum, the number and pattern of the ridges on the carapace and pleon, the shape of thoracic sternite 3 and the armature of the P2–4 dactyli. A dichotomous identification key to all species is provided.